Acquisition of Russian gender agreement by monolingual and bilingual children. (December 2015) - Schwartz, Mila; Minkov, Miriam; Dieser, Elena; Protassova, Ekaterina; Moin, Victor; Polinsky, Maria
Aim and Objectives/Purpose/Research Questions: The main goal of this study was to examine noun–adjective gender agreement in Russian by comparing bilingual children with diverse L2 backgrounds (English, Finnish, German, and Hebrew) with age-matched monolingual children and monolinguals one year younger. This comparison was made to investigate the influence of L2 grammar on the acquisition of gender agreement by (L1) Russian-speaking children. Design/Methodology/Approach: The participants included four groups of 4–5-year-old bilingual children with Russian as L1 and English, German, Finnish, or Hebrew as L2, who were compared to monolingual children in Russia in two age groups (3–4 and 4–5 years old). The children were matched by socioeconomic status and parents' educational background. All children were tested individually during one testing session. Agreement data were elicited using a semi-structured elicitation test, with verbal and visual stimuli. Data and Analysis: We used qualitative data analysis to identify types and categories of errors, and quantitative data analysis to compare the tendencies of noun–adjective gender agreement in Russian (L1) between the groups. Findings/Conclusions: Development of gender agreement in the bilingual children from different L2 backgrounds was qualitatively similar to that of the 3–4-year-old monolingual Russian-speaking children. This result suggests that bilingual development in L1 follows the same developmental path as monolingual development, albeit with a delay. In addition, bilingual children whose L2 has grammatical gender (German, Hebrew) outperformed the other bilinguals on gender agreement, indicating that the presence of a grammatical category in both languages spoken by a bilingual facilitates category acquisition. Originality and Significance/Implications: The study contributes to the discussion on how the transparency and phonological saliency might affect the bilingual children's acquisition of inflectional morphology and on how influence of L2 on L1 might in some cases help and in other cases impede the acquisition of L1.